Curcumin analogue 1,5-BIS(4-hydroxy-3-methoxyphenyl)-1,4-pentadiene-3-one alters protein expression patterns in HPV16-infected cervical cancer cells (Funded work) - JIN HUNG CHEW; FELICIA PAULRAJ; FARIDAH ABAS; NORDIN H. LAJIS; IEKHSAN OTHMAN; RAKESH NAIDU (International Journal of Pharma and Bio Sciences, 2017)
Curcumin analogue 1,5-bis (4-hydroxy-3-methoxyphenyl)-1,4-pentadiene-3-one (MS13) has been shown to exhibit significant cytotoxic and anti-proliferative activity. In the present study, protein expression profile of MS13-treated HPV-16 positive CaSki human cervical cancer cells was determined using two-dimensional gel electrophoresis and identified differentially expressed proteins by mass spectrometry. Eighty two up-regulated and 11 down-regulated proteins were identified in response to 48 h of 3.5µM MS13 treatment. Functional analysis revealed that the highly up-regulated proteins were associated with metabolic process (CAPNS1, PDXK, MTHFD1, ACADVL and NPM1), cell communication (ARHGDIB), cell cycle and apoptosis (LMNA), transcriptional regulation (SRSF1 and SRSF7) and translational regulation (DDX47) whereas highly down-regulated proteins were associated with metabolic process (ALDOA, ATP5B and ANXA5), protein folding (HSP90B1 and HSP90AB2P), structural molecule activity (ACTN4) and transcriptional regulation (HNRNPL). These findings revealed that MS13 may exhibit its anticancer properties on cervical cancer cells through regulation of these proteins.